Hybrid LIMA to LAD for Survival - Vinall, Phil (MD Conference Express, 2011)
This article discusses the pros and cons of hybrid coronary revascularization, and the need for hybrid operating suites with surgical and fluoroscopic capabilities to support the performance of this procedure.